Strength band training - Page, Phillip 1967-; Ellenbecker, Todd S. 1962- (Human Kinetics, 2020)
The top resource on strength band training is now expanded, updated, and better than ever! Whether you are training in the gym, at home, or on the road, Strength Band Training will show you how to maximize strength, speed, and flexibility. Featuring more than 160 exercises and 27 fitness and sport-specific workouts, you will discover why strength bands are the ultimate tool for targeting, isolating, rehabilitating, and developing every major muscle group.